The Sorong Fault Zone Kinematics: Implication for Structural Evolution on Salawati Basin, Seram and Misool, West Papua, Indonesia - Riadini, Putri; Sapiie, Benyamin; Surya Nugraha, A.M. (Ikatan Ahli Geologi Indonesia, 2012)
The Sorong Fault Zone (SFZ) is an active left lateral fault system that active since the Late Miocene. The SFZ is located in the northern margin of Papua, Indonesia, extended thousand kilometers from the Eastern part of the island to the Bird's Head region. Our new model indicates that SFZ moved the Bird's Head area, including Salawati Basin to the west, related to the movement of the Pacific Plate. The movement of SFZ involves rotation and translation that separates Salawati Basin from the Bird's Head region with basement high as the boundary of the basin, and also give an implication to the evolution of Seram Fold Thrust Belt (SFTB) and Misool Onin Kumawa Anticline (MOKA).More than 200 seismic lines have been interpreted along Seram, Misool, and Salawati offshores. These interpretations show the development of listric and planar normal faulting at Western part of Misool island and flower structure at NW Bird's Head region. This faulting activity was interpreted as a result of SFZ activities, which cut Paleozoic through the Tertiary formations. The listric and planar normal fault in the Salawati Basin explains the block rotation mechanism that related to the Bird's Head movement to the west. In addition, flower structures that observed at NW Bird's Head indicate the shortening effect of the SFZ activities. Seemingly, rotation and translation of SFZ to the west are associated with the evolution of SFTB that indicate by NESW shortening perpendicular to the island. The deformation in the SFTB showed the development of fold-thrust belt structure at Seram Trough area, which repeated the Mesozoic-Miocene sequences, with the detachment surface located between Seram and Seram Trough. Reverse fault at Mesozoic through Miocene sequences in the north of the trough and at Misool area are reactivated normal faults formed during the NW shelf of Australia rifting since the Mesozoic. Therefore, SW directed shortening as a response of the Bird's Head region movement combined with additional westward movement of Tarera-Aiduna strike-slip system forms the SFTB.New seismic interpretations combined with palinspastic reconstruction suggest that there are rotation and translation phase in relation to SFZ mechanism that develops the Salawati Basin, MOKA, and SFTB. These deformations mechanism are active since the Late Miocene related to the collision between Pacific island arc complexes and passive margin of the NW Australian plate.